(untitled) (Research, Society and Development, 2022)
The use of licit and illicit drugs has grown in recent years and constitutes a serious public health problem in the world, where the use of psychoactive drugs is responsible for more than 400 thousand deaths annually, and contributes significantly to HIV/AIDS epidemics. , viral hepatitis B and C and tuberculosis, the objective of the study was to draw a chronological timeline on the care of chemically dependent patients in the period from 2001 to 2019. The research is a documentary analysis, retrospective, exploratory descriptive type, with a qualitative approach. It was evidenced that the changes in the National Policy on Drugs of 2019 are characterized as a setback in the achievements established through the psychiatric reform, extinguishing harm reduction and instituting abstinence as a central point of treatment. expansion of knowledge about the policy of alcohol and other drugs, the factors that permeate the exacerbated consumption of illicit substances and the attention given to chemical dependents in Brazil.